Hydroamination of alkynes catalyzed by NHC-Gold(I) complexes: the non-monotonic effect of substituted arylamines on the catalyst activity - Sirignano, Marco; D’Amato, Assunta; Costabile, Chiara; Mariconda, Annaluisa; Crispini, Alessandra; Scarpelli, Francesca; Longo, Pasquale (Frontiers in Chemistry, 2023)
Imines are valuable key compounds for synthesizing several nitrogen-containing molecules used in biological and industrial fields. They have been obtained, as highly regioselective Markovnikov products, by reacting several alkynes with arylamines in the presence of three new N-Heterocyclic carbene gold(I) complexes (3b, 4b, and 6b) together with the known 1-2b and 7b gold complexes as well as silver complexes 1-2a. Gold(I) complexes were investigated by means of NMR, mass spectroscopy, elemental analysis, and X-ray crystallographic studies. Accurate screening of co-catalysts and solvents led to identifying the best reaction conditions and the most active catalyst (2b) in the model hydroamination of phenylacetylene with aniline. Complex 2b was then tested in the hydroamination of alkynes with a wide variety of arylamines yielding a lower percentage of product when arylamines with both electron-withdrawing and electron-donating substituents were involved. Computational studies on the rate-determining step of hydroamination were conducted to shed light on the significantly different yields observed when reacting arylamines with different substituents.